Economic performance and natural resources commodity prices volatility: Evidence from global data. (September 2022) - Yating, Yang; Mughal, Nafeesa; Wen, Jun; Thi Ngan, Truong; Ramirez-Asis, Edwin; Maneengam, Apichit
Abstract: The current research study aims to investigate natural resources, commodity prices volatility and global economic performance covering the period from 1970 to 2021. This study uses various variables, i.e., total natural resources volatility (TNR), crude oil price (CR), oil rents (OR), and natural gas rents (NGR), to measure natural resources price volatility. This study uses the wavelet approach for empirical investigation of causal association in the short and long run. The empirical estimations of the wavelet power spectrum reveal that all the variables are vulnerable, specifically in global crisis events. Besides, the wavelet coherence approach indicates a bidirectional causal association exists between natural resources commodity price volatility (TNR, OR, NGR) and global economic performance. However, the causal impact of natural resources price volatility is found only in the short-run, while economic performance significantly causes volatility in natural resources price in the long run. Moreover, the wavelet coherence authenticates unidirectional causal association running from global economic performance to CR in both the short-run and long-run. This study provides some policy insights which could have essential economic and natural resources price volatility control measures for policy-makers and future researchers. Highlights: Global economic performance and natural resource price volatility are investigated. This study used wavelet power spectrum and wavelet coherence techniques. Significant vulnerabilities have been found in all the variables between 1970 and 2021. Two-way causality is found between economic performance and prices' volatility. One-way causality is seen running from economic performance to crude oil price.